2008
DOI: 10.1007/s10534-008-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Rhodotorula sp. Y11 to cadmium

Abstract: Some aspects of the cellular responses to cadmium were extensively investigated in the yeast Rhodotorula sp. Y11. Scanning electron microscopy indicated that accumulation of cadmium in the Y11 did not cause any visible effects on cell morphology. More than 20% yeast cells still showed viability after 15 h of cadmium accumulation under 100 mg l(-1) cadmium concentration, and transmission electron microscopy analysis showed that plasmolysis and thickened cell wall were not observed in all of the cells. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…The yeast Rhodotorula sp. Y11 (Li and Yuan, 2008), Phytophthora nicotianae hyphae (Blackman et al, 2005), Rhizopogon roseolus (Miszalski et al, 1998) contained only MnSOD isozymes. Colletotrichum graminicola have three SOD types (Fang et al, 2002).…”
Section: Comparison Of Edible Mushroom Sod On Thermostabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast Rhodotorula sp. Y11 (Li and Yuan, 2008), Phytophthora nicotianae hyphae (Blackman et al, 2005), Rhizopogon roseolus (Miszalski et al, 1998) contained only MnSOD isozymes. Colletotrichum graminicola have three SOD types (Fang et al, 2002).…”
Section: Comparison Of Edible Mushroom Sod On Thermostabilitymentioning
confidence: 99%
“…Studies of SODs from microbes, animals and plants have been reported (Bridges and Salin, 1981;Bannister et al, 1987;Michalski, 1996;Zbigniew and Wojciech, 2006;Chakrabarty et al, 2007;Li and Yuan, 2008;Seckin et al, 2009), but to our knowledge, little information is available about this enzyme in edible mushrooms. Hence, the objective of this study is to evaluate the SODs of 17 edible mushroom species, including their activity, thermostability and characterisation of SOD isozymes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that cell walls contributed to metal ion tolerance in fungi, such as Cd, Zn, Ni, Cu and Hg resistance [3539]. Al stress also led to the increased thickness of the cell walls in Rhodotorula sp.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of lead and cadmium by R. rubra biomass was tested (SALINAS et al, 2000), as well as the removal of nickel by planktonic cells of Rhodotorula sp. (LI and YUAN, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the heavy metal tolerance and the removal potential for Cd 2+ , Zn 2+ and Ni 2+ have been focused on planktonic cells of Rhodotorula species, exclusively (SALINAS et al, 2000, REZZA et al, 2001, LI and YUAN, 2008, SUAZO-MADRID et al, 2011, SAN and DÖNMEZ, 2012. Only one study has reported heavy metal removal efficiency for Zn 2+ by Candida rugosa and Cryptococcus laurentii biofilms (BASAK et al 2014).…”
Section: Introductionmentioning
confidence: 99%